Study of the Effect of Zakat on Reducing Poverty in Districts/Cities in Aceh Province 2011-2018 - Nilam Sari; Winny Dian Safitri; Rizki Maulana; Jumila Jumila; Elda Elnovita (Proceedings of AICS - Social Sciences, 2020)
Poverty is a condition in which someone is unable to fulfill his primary needs. Poverty is caused by low human resources, lack of access to capital, and low levels of productivity of goods and services. One indicator of reducing the poverty rate can be done by optimizing zakat funds. The purpose of this study is to determine whether the existence of zakat funds can reduce poverty. This is quantitative research that used secondary data, and the data was analyzed by using the panel data regression technique. The results showed that zakat has a significant negative effect on the poverty rate. The result implies that zakat can be used as an instrument of fiscal policy by district/city governments in combating poverty rate.